1994
DOI: 10.1044/jshr.3701.106
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Input Effects on Word Comprehension of Children With Specific Language Impairment

Abstract: Children with specific language impairment (SLI) are known to have limited lexicons. Previous studies implicate a possible processing problem, in the form of a limited ability to comprehend new words in settings that require Quick Incidental Learning (QUIL). This study investigates further the factors contributing to limited QUIL by examining the effects of input frequency and word type (nouns vs. verbs). In addition, immediate versus long-term memory was examined for possible problems with storage mechanisms.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
257
10
19

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 287 publications
(304 citation statements)
references
References 25 publications
18
257
10
19
Order By: Relevance
“…There is evidence that even very young TD children demonstrate such retention after shared book reading experiences, as reported by Horst et al (2011). QUIL studies of young children with SLI, on the other hand, suggest that there may be particular problems with retention, especially with verbs (Oetting, 1999;Rice et al, 1994). In a silent reading context, Wagovich et al (2012) reported good retention of orthographic PWK among both lower and higher language groups after a delay of 2-3 days.…”
Section: Retention Of Incidental Word Learningmentioning
confidence: 63%
See 3 more Smart Citations
“…There is evidence that even very young TD children demonstrate such retention after shared book reading experiences, as reported by Horst et al (2011). QUIL studies of young children with SLI, on the other hand, suggest that there may be particular problems with retention, especially with verbs (Oetting, 1999;Rice et al, 1994). In a silent reading context, Wagovich et al (2012) reported good retention of orthographic PWK among both lower and higher language groups after a delay of 2-3 days.…”
Section: Retention Of Incidental Word Learningmentioning
confidence: 63%
“…In contrast, Horohov and Oetting (2004) found that scores for verbs were significantly higher than for nouns among young children with SLI as well as both age-matched and language-matched controls. In a similar vein, Rice et al (1994) reported that after 10 repetitions, both TD and SLI groups learned more verbs than nouns. Clearly, it is not a simple case of nouns being easier to learn from oral exposures than verbs, either for TD children or those with SLI.…”
Section: Part Of Speech and Pwk Growthmentioning
confidence: 66%
See 2 more Smart Citations
“…In terme van die aanleer van leksikale items het Rice en kollegas (Oetting, Rice, en Swank 1995;Rice, Buhr, en Nemeth 1990;Rice, Buhr, en Oetting 1992;Rice, Oetting, Marquis, Bode, en Pae 1994) gevind dat STG-kinders op sogenaamde "fast-mapping"-take swakker as ouderdomkontroles vaar, met werkwoorde wat die mees problematies vir STG-kinders is.…”
Section: Leksikonunclassified